Bank credit supply and firm innovation - Marek Giebel; Kornelius Kraft (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We analyze the causal effect of the credit supply shock to banks induced by interbank market disruptions in the recent financial crisis 2008/2009 on their business customers' innovation activity. Using a matched bank-firm data set for Germany, we find that having relations with a more severely affected bank seriously hampers firms' current innovation activities due to funding shortages. Furthermore, we find that firms with a relationship to a less severely affected bank are more likely to initiate new product and process innovations and to reallocate human resources to innovation during the financial crisis.
urn:nbn:de:bsz:180-madoc-447651
Keywords: G01; G21; G30; O16; O30; O31; 330; financing of innovations; credit supply; financial crisis; innovative activities